A hybrid consensus algorithm for master–slave blockchain in a multidomain conversation system - Yang, Wenli; Garg, Saurabh; Huang, Zhiqiang; Kang, Byeong (Expert systems with applications, 2022)
•Build a master–slave chain model for a multi-domain conversation system.•A new hybrid consensus algorithm is proposed for designed master–slave chain.•Performance of the proposed approach is evaluated to verify the feasibility and effectiveness. Conversation systems play an important role in the research and development of multidomain systems, in which the number of conversations increases rapidly with the number of domains. Multiple experts must maintain these conversation interactions, otherwise experts from different domains are unable to interact properly. For this reason, ensuring secure and efficient cooperation between different experts has become a serious issue that needs to be resolved. This study proposes a hybrid consensus algorithm for a master–slave chain to improve the efficiency and scalability of multidomain conversation interactions. Firstly, we build a master–slave chain model for a multidomain conversation system which can be applied to process multiple conversation interactions from different domains concurrently. Subsequently, a new hybrid consensus algorithm is proposed which combines reputation-driven voting, dynamic construction strategies and an incentive scheme with both economic and non-economic rewards. Implemented and tested on a local private blockchain network, the experimental results demonstrate the feasibility and effectiveness of the proposed approach, in order to offer a decentralised, scalable, multidomain conversation system in a secure manner.